Tissue Factor-Independent Coagulation Correlates with Clinical Phenotype in Factor XI Deficiency and Replacement Therapy - Bertaggia Calderara, Debora; Zermatten, Maxime G.; Aliotta, Alessandro; Batista Mesquita Sauvage, Ana P.; Carle, Vanessa; Heinis, Christian; Alberio, Lorenzo (Thrombosis and Haemostasis, 2020)
Background In factor XI (FXI) deficiency, bleeding cannot be predicted by routine analyses. Since FXI is involved in tissue factor (TF)-independent propagation loop of coagulation, we hypothesized that investigating the spatiotemporal separated phases of coagulation (TF-dependent and -independent) could improve diagnostics.Objectives This article investigates the correlation of parameters describing TF-dependent and -independent coagulation with the clinical phenotype of FXI deficiency and their ability to assess hemostasis after FXI replacement.Methods We analyzed: (1) plasma from healthy controls (n = 53); (2) normal plasma (n = 4) spiked with increasing concentrations of a specific FXI inhibitor (C7P); (3) plasma from FXI-deficient patients (n = 24) with different clinical phenotypes (13 bleeders, 8 non-bleeders, 3 prothrombotics); (4) FXI-deficient plasma spiked with FXI concentrate (n = 6); and (5) plasma from FXI-deficient patients after FXI replacement (n = 7). Thrombin generation was measured with the reference method calibrated automated thrombogram and with Thrombodynamics (TD), a novel global assay differentiating TF-dependent and -independent coagulation.Results C7P dose-dependently decreased FXI activity, prolonged activated partial thromboplastin time, and hampered TF-independent coagulation. In FXI-deficient bleeders, TD parameters describing TF-independent propagation of coagulation and fibrin clot formation were reduced compared with controls and FXI-deficient nonbleeders and increased in FXI-deficient patients with prothrombotic phenotype. Receiver operating characteristic analysis indicated that TF-independent parameters were useful for discriminating FXI-deficient bleeders from non-bleeders. In FXI-deficient plasma spiked with FXI concentrate and in patients receiving FXI replacement, TD parameters were shifted toward hypercoagulation already at plasma FXI levels around 20%.Conclusion TF-independent coagulation parameters assessed by TD have the potential to identify the clinical phenotype in FXI-deficient patients and to monitor FXI replacement therapy.
Keywords: bleeding; FXI deficiency; global hemostasis assay; Hemoleven; thrombin generation